Legal Arrangement Concerning Regional Unit Price Standards Its Impact to Financial and Administrative Rights of Regional People's Representative Council - Yogi Yasa Wedha; Edy Nurcahyo; Hudali Mukti (Jurnal Hukum Volkgeist, 2023)
Constitution in the government system of the Republic of Indonesia adheres the concept of trias politica, which is a concept stating that power is not transferred to the same person/institution, to prevent abuse of power and to guarantee human rights of citizens. The concept of trias politica is applied in the form of three institutions, namely executive, legislative and judicial institutions. These three institutions have different duties, rights, obligations, and responsibilities according to their authority. It turns out, however that the aim of preventing abuse of power by means of power distribution is not running well and there has been an overlap of authority among the institutions. This research is the author's study of the Legal Arrangements concerning Regional Unit Price Standards upon the issuance of Presidential Regulation Number. 33 of 2020 concerning Regional Unit Price Standards, its impact to Financial and Administrative Rights of the chairman and members of the Regional People's Representative Council. It is a normative legal research applying statutory approach, conceptual and comparative approaches. It was concluded that the placement of legislature as a quasi-executive results in the legislature shall comply with every regulation issued by the executive, this causes in an overlap of authority between the executive and the legislative institutions